Circulating Plasma MicroRNAs As Diagnostic Markers for NSCLC - Hou, Jinpao; Meng, Fei; Chan, Lawrence W. C.; Cho, William C. S.; Wong, S. C. Cesar (Frontiers in Genetics, 2016)
Lung cancer is the most common cause of cancer deaths all over the world, in which non-small cell lung cancer (NSCLC) alone accounts for ~85% of cases. It is well known that microRNAs (miRNAs) play a critical role in various cellular processes, mediating post-transcriptional silencing either by mRNA degradation through binding the 3’ UTR of target mRNA or by the translational inhibition of the protein. In the past decade, miRNAs have also been increasingly identified in the biological fluids such as human serum or plasma named as circulating or cell-free miRNAs, and may function as non-invasive diagnostic markers of cancers including NSCLC. Circulating tumor cells (CTCs), a non-invasive “liquid biopsy”, are those cells that are shed from solid tumors and then migrate into the circulation. However, reports concerning the role of CTCs are quite rare, which may be attributed to the difficulties in the enrichment and detection of CTCs in the circulation. Although there have been reassuring advances in identifying circulating miRNA-panels, which is assumed to be of diagnostic value in NSCLC early stage, some issues remain concerning the reliability of using miRNA panels as a diagnostic tool for NSCLC. In the current review, we are aiming at providing insights into the miRNAs biology, the mechanisms involved in the miRNAs release into bloodstream, cell-free miRNAs as the diagnostic marker of NSCLC, and the current limitations of CTCs as diagnostic markers in NSCLC.